Penerapan Model Pembelajaran Make a Match untuk Meningkatkan Hasil Belajar Siswa Kelas IV pada Pelajaran IPAS di SD Negeri 2 Kasturi - Komala, Widiani Ica; Yulianengsih, Neng Lia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to desribe the research plan for the application of the make a match learning model to improve the learning outcomes of fourth grade students in science lessons at SD Negeri 2 Kasturi before and after the make a match learning model wa implemented. The rearch method used was a quantitative method, this type of research wa pre-experimental with a one-group pretest posttest design. Sampling in this study used a total sampling teshnique. This study involed 39 fourt-gade students of SD Negeri 2 Kasturi. Data colletion was carried out with a pre-test and a final test of 20 questions, observation, interview, and documentation. The result of the study showed that the make a match learning model can improve student learning outcomes. From the hypothesis test with the testing criteria if the sig. (2-tailed) value < 0.05, then Ho is rejected and Ha is a accepted with a signitificance level= 0.05, a value of 0.000 is obtaned so that it can be concluded that it can be rejected and Ha is accepted, and the level of effectiveness is proven bt the N-gain score test of 0.07458 with high criteria and N-gain percent test of 74.57 with quite effective criteria. This shows that the application of the make a match learning model is effective in improving student learning outcomes.